Biocatalytic Routes to Enantiomerically Enriched Dibenz[c, e]azepines. Issue 49 (7th November 2017) - France, Scott P.; Aleku, Godwin A.; Sharma, Mahima; Mangas‐Sanchez, Juan; Howard, Roger M.; Steflik, Jeremy; Kumar, Rajesh; Adams, Ralph W.; Slabu, Iustina; Crook, Robert; Grogan, Gideon; Wallace, Timothy W.; et al.
Abstract: Biocatalytic retrosynthetic analysis of dibenz[c, e]azepines has highlighted the use of imine reductase (IRED) and ω‐transaminase (ω‐TA) biocatalysts to establish the key stereocentres of these molecules. Several enantiocomplementary IREDs were identified for the synthesis of ( R )‐ and ( S )‐5‐methyl‐6, 7‐dihydro‐5 H ‐dibenz[c, e]azepine with excellent enantioselectivity, by reduction of the parent imines. Crystallographic evidence suggests that IREDs may be able to bind one conformer of the imine substrate such that, upon reduction, the major product conformer is generated directly. ω‐TA biocatalysts were also successfully employed for the production of enantiopure 1‐(2‐bromophenyl)ethan‐1‐amine, thus enabling an orthogonal route for the installation of chirality into dibenz[c, e]azepine framework. Abstract : No IRE intended : Biocatalytic retrosynthetic analysis of dibenz[ c, e ]azepines highlights the use of imine reductase (IRED) and ω‐transaminase (ω‐TA) biocatalysts to establish key stereocentres of these molecules. Enantiocomplementary IREDs were identified for the synthesis of enantiopure dibenz[ c, e ]azepines. Crystallographic evidence suggests that IREDs may be able to bind one conformer of the imine substrate. Boc= tert ‐butoxycarbonyl.